Landscapes Vulnerability on Climate Change in Yogyakarta Province, Indonesia. Issue 1 (November 2021) - Wacano, D; Latifah, N D; Bishop, H; Gutama, H; Hasanah, N A I; Yulianto, A; Rahmawati, S; Nurmiyanto, A; Putra, H P; Maziya, F B; Ardhayanti, L I; Lathifah, A N; et al.
Abstract: Whether climate change is real or not, the daily basis phenomena and its evidences should be our concern nowadays. Yogyakarta is one of the provinces that are vulnerable to the impact of climate change in Indonesia. The specific responses to climate change phenomena in Yogyakarta province are indirectly correlated to landscape characteristics. These characteristics are important aspects for the assessment and development of new approaches to address the impacts of climate change. Therefore, this paper presents the status of landscape vulnerability to climate change in Yogyakarta province to consider the issues of mitigation and adaptation to climate change. Analytical hierarchy process (AHP) was applied to determine the objective of the research. The results of previous studies were reviewed in depth and combined with field observations to build a strong argument before evaluating the matrices and weights in the AHP steps. The result analysis showed that the most vulnerable landscape in Yogyakarta province is the anthropogenic landscape, which is located in Yogyakarta city. Furthermore, the combination of population density and poor sanitation management should be considered as a factor in mitigating and adapting to climate change in Yogyakarta city.